The Social Dynamics of the Characters in a Short Stories Collection of Mata yang Enak Dipandang by Ahmad Tohari - Arumndani, Batari; Supriyanto, Teguh; Doyin, Mukh (Universitas Negeri Semarang, 2021)
This study aimed to analyze a short stories collection of Mata yang Enak Dipandang that contains a variety of living spaces that grow and develop in a civilized environment. The short story collection had presented various social problems. The social problem was the social dynamics of multiple things that did not follow cultural values or human behavior habits in general. The purpose of this study was (1) to describe the shape of social dynamics that appeared in Ahmad Tohari’s short stories collection of Mata yang Enak Dipandang. (2) to describe the social dynamics problems experienced by the characters in Ahmad Tohari’s short stories collection of Mata yang Enak Dipandang. This research used the sociology of literature approach. Data collection in this study used the study of literature and the first level reading technique, namely heuristics. The method of analyzing data had done by hermeneutic reading. The study results showed that a short stories collection of Mata yang Enak Dipandang contained (1) five forms of social dynamics, namely slow changes, small changes, significant changes, desired changes, and unwanted changes. (2) there were two problems: the increase or decrease of the population and the community conflict in the social dynamics of the collection of short stories from Mata yang Enak Dipandang.